Impact study on model livestock community development programme in some selected areas of Bangladesh - Uddin, MT; Islam, MM; Nasrin, M (Bangladesh Journal of Livestock Research, 2020)
With a view to increase the productivity of existing backyard livestock and poultry production systems and thereby to improve the socio-economic status of the rural people, BLRI in collaboration with the Department of Livestock Services (DLS) initiated the study since April 2010. The specific objectives of the study were to disseminate the livestock technologies for increasing productivity through training and demonstration and to assess the impact of technological interventions on livestock productivity, socioeconomic improvement and changing livelihood status of rural farm families. The study was implemented initially at Kadamtoli under Belkuchi Upazila under Serajganj district and Chakpara and Bichamara villages under Naikhongchari Upazila under Banderban district which was later extended to Talukhabu village of Gongachara Upazila under Rangpur district. Through this project, technological support was provided to a total of 321, 218 and 780 farm households in Belkuchi, Naikhongchari and Gangachara upazila, respectively. In order to conduct the impact study, 90 farmers taking 30 from each Upazila were selected through simple random sampling technique. The ‘before’ and ‘after’ comparison was followed for assessing the impact. The t-statistic was applied to test the significance of relevant parameters. It was revealed that technological intervention has resulted to increase in livestock and poultry population and increase in productivity of milk (19-40%), duck and chicken eggs (22-36%) both horizontally and vertically. There was no occurrence of death of cattle, goat and poultry birds. Farmer’s overall income was boosted up which has contributed to possession of new household assets and addition of the already available assets. The consumption of all food items was increased as well. It was recommended that the programme may be replicated to other locations with new interventions. Bangladesh J. of Livestock Res. 20(1-2): 88-100, Jan-Dec 2013